Zagotavljanje pravilnosti sestave in objave letnega poročila - 60.a člen ZGD-1 - Podgorelec, Peter (Podjetje in delo, 2013)
In the article the author discusses the obligations of members of management and supervisory bodies in relation to bookkeeping, composing and publishing of annual and consolidated annual reports and liability pertaining to violations of the above, ranging from criminal to civil. Provisions of Article 60.a, added to ZGD-1 with the implementation of Directive 2006/46/EC by means of amendment ZGD-1B, only confirmed the collective nature of duties, a principle that has been known in Slovenian corporate law before. Along with concretization of duties and raising the issue of how the collective principle is implemented in the case of interior distribution of tasks among members of management and supervisory bodies, special attention is also paid to the obligation of certification - a relatively new institute. Special emphasis is placed on the role of annual report auditor and internal auditor and the importance of their cooperation with a supervisory body or audit committee.
Keywords: finančno upravljanje; gospodarske družbe; letna poročila; nadzorni sveti; poslovne knjige; uprava